Formación profesional y su competencia laboral de egresados de las escuelas profesionales de derecho en la región andina - William Pacori, Edwerson (2022)
The accumulation of knowledge and skills leads to labor insertion through updated and specialized training. The study aimed to establish the difference between the professional training and labor competence of graduates from law professional schools in the Andean region. Using a quantitative approach and a comparative descriptive design, a sample of 210 intentionally selected graduates was surveyed using a questionnaire for professional training and a psychometric test for labor competence. The results showed that the National University of the Altiplano (UNA) had adequate professional training followed by the Andean University Nestor Caceres Velasquez (UANCV), compared to San Carlos University (USC) and finally Alas Peruanas University (UAP). It is inferred that the professional training imparted in law professional schools in the Andean region has significant differences (NS=0.000), leading to indistinct labor competencies.